The Actor Domination in the Collaborative Governance in the Lampung Province Central Government Displacement Policy: An Ambivalent - Mukhlis, Maulana; Nazsir, Nasrullah; Rahmatunnisa, Mudiyati; Yani Yuningsih, Neneng (Jurnal Ilmiah Peuradeun, 2018)
The objective of this article is to explain the ambivalent existence related to actor domination in the collaborative governance. As a precondition for the collaborative governance process, domination is a factor which must be prevented to maintain equality and mutual trust between actors. Therefore, the core question of this article is that is it true that the actor domination has negative effects to the collaboration sustainability? This article was written by using qualitative method. Data were collected with deep interviews, document studies, and literary studies and data were analyzed by using descriptive technique. The case of Lampung province central government displacement in 2004-2016 was made to be a research basis to answer the core question. The research finding showed that actor domination was dilemmatic. The collaboration process was in fact very dependent on the main actor who “control” the collaboration process, both in the planning stage (through Planning Coordination Team) and in implementation stage (through forum of Region Management Agency). This finding was very important because in spite of violating equality between actors, the actor domination in this policy case was beneficial. The inequality which was assumed to produce mutual untruths was not proven. In conclusion, actor domination is an ambivalent; something that must be prevented, but it then becomes a key factor. In what situation this actor domination gives a meaning? This article tries to answer it.